Synthesis of robust interconnected power system stabilizers for turbine generators in sugar factories - Kuievda, Yulia; Baliuta, Serhii (My University, 2017)
This research aims to develop the method of synthesis of interconnected robust power system stabilizer (IRPSS) for power supply systems of sugar factories with own turbine generators. A model of power supply system with own generator, automatic exciter regulator, turbine and speed governor is constructed. The controlled object nonlinear differential equations model is linearized and simplified by reducing of its order using Schur's method. The model is extended with chosen weighting functions preparing for H∞ synthesis procedure. The LMI region is chosen in the form of a conic sector for satisfying condition of lower oscillability of transient process, which is the main goal of such a regulator to optimize turbine generator operation process. The IRPSS for extended model was synthesized, using H∞ synthesis procedure with poles placement. The regulator is presented in the form of matrix continuous transfer function. The transition process of 3-phase short-circuit fault behind the transformer and subsequent automatic re-closing is simulated with full-order nonlinear model with IRPSS and compared with standard system stabilizer and the system without stabilizer. The graphs of modelled transients demonstrate effectiveness of IRPSS.
Keywords: regulator; synthesis; turbogenerator; регулятор; синтез; турбогенератор; кафедра електропостачання і енергоменеджменту